English, asked by supriyapujahari4, 5 months ago

Hola Brainlians. Here's a question to check your Trigonometric skill. ICSE Board : Inverse Trigonometry, Class 10. Give answer fast and no spam.

Proof the given identity.

3tan^{-1}x = sin^{-1} [(2x)/(1 + x²)] , |x| ≤ 1

Spammers stay away. No spam. Give best answer. Mods and stars answer.​

Answers

Answered by IdyllicAurora
13

Correct Qúestion :-

Prove the following identity :-

\;\bf{\odot\;\;\green{2\tan^{-1}\:x\;=\;\sin^{-1}\dfrac{2x}{1\:+\:x^{2}}}}

______________________________________

Concept :-

Here the concept of Trigonometric Identities have been used. This is the question of Inverse Trigonometry. So the easiest method to solve such questions is using an assumption. Just assume a variable with a key value. Then we can initialise the equation and thus find the answer. Also we shall be using different trignometric equations in this.

Let's do it !!

_____________________________________

Solution :-

Let tan¯¹ x = y

This will give us, x = tan y

Now let's apply this value of x in the R.H.S of the equation to be proved .

\;\tt{\rightarrow\;\;R.H.S.\;=\;\sin^{-1}\dfrac{2x}{1\:+\:x^{2}}}

By applying value here, we get

\;\tt{\rightarrow\;\;R.H.S.\;=\;\sin^{-1}\dfrac{2(\tan y)}{1\:+\:(\tan y)^{2}}}

\;\tt{\rightarrow\;\;R.H.S.\;=\;\sin^{-1}\dfrac{2\tan y}{1\:+\:\tan^{2}y}}

Now by another trignometric identity, we know that,

\;\sf{\leadsto\;\;\sin 2x\;=\;\dfrac{2\tan x}{1\:+\:\tan^{2} x}}

  • Here x = y

By applying this, we get

\;\tt{\rightarrow\;\;R.H.S.\;=\;\sin^{-1}(\sin 2y)}

Now sin¯¹ and sin will cancel out each other.

\;\tt{\rightarrow\;\;R.H.S.\;=\;1\:\times\:2y}

\;\bf{\rightarrow\;\;R.H.S.\;=\;2y}

Now let's apply the value of y. We get,

\;\bf{\rightarrow\;\;R.H.S.\;=\;2(\tan^{-1} x)}

\;\bf{\rightarrow\;\;\blue{R.H.S.\;=\;2\tan^{-1} x}}

Let's now compare LHS and RHS.

Clearly, LHS = RHS.

\;\bf{\rightarrow\;\;\red{L.H.S.\;=\;R.H.S.\;=\;2\tan^{-1}x}}

By applying initial values, this will give us,

\;\bf{\mapsto\;\;\purple{2\tan^{-1}\:x\;=\;\sin^{-1}\dfrac{2x}{1\:+\:x^{2}}}}

Hence, Proved.

________________________________

More to know :-

sin 2x = 2 sin x cos x

cos 2x = 2 cos² x - 1 or 1 - 2 sin² x

sin 3x = 3 sin x - 4 sin³ x

cos 3x ° 4 cos³ x - 3 cos x

sin² x - sin² y = sin(x + y) • sin(x - y)

2 cos C cos D = cos(C + D) + cos(C - D)

-2 sin C sin D = cos(C + D) - cos(C - D)

2 cos C sin D = sin(C + D) - sin(C - D)

2 sin C cos D = sin(C + D) + sin(C - D)

Answered by amarjyotijyoti87
1

Answer:

Answer in the attachment.

Attachments:
Similar questions